Legal protection to consumers of fresh food of imported plant origin - Muhamad Musyaffak Fauzi; Made Warka; Slamet Suhartono; Endang Prasetyawati (Technium Social Sciences Journal, 2022)
This research is a normative legal research. After the enactment of Law No. 18 Th. 2012 Concerning Food, in particular the enactment of Decree of the Minister of Agriculture Number: 55/PERMENTAN/KR.040/11/2016 concerning Food Safety Supervision of Importation of Fresh Food from Plants Juncto Government Regulation Number 86 of 2019 concerning Food Safety Preventive legal protection for PSAT consumers suffers from decrease or be degraded, because imported PSAT is not subjected to laboratory testing in the country of origin to determine the content of biological or chemical contaminants, only if PSAT circulated in Indonesia is proven to contain biological and/or chemical contaminants, the PSAT is withdrawn from circulation.